2019
DOI: 10.1155/2019/1346987
|View full text |Cite
|
Sign up to set email alerts
|

Remote Technology-Based Training Programs for Children with Acquired Brain Injury: A Systematic Review and a Meta-Analytic Exploration

Abstract: Introduction. Multidisciplinary rehabilitation interventions are considered to be a need for children with acquired brain injury (ABI), in order to remediate the important sequelae and promote adjustment. Technology-based treatments represent a promising field inside the rehabilitation area, as they allow delivering interventions in ecological settings and creating amusing exercises that may favor engagement. In this work, we present an overview of remote technology-based training programs (TP) addressing cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 86 publications
1
47
0
1
Order By: Relevance
“…Technology-based treatments represent a promising field for multidisciplinary rehabilitation of children with acquired brain injury (ABI). Corti et al ( 22 ) underlined in a recent review that telerehabilitation is promising to enhance cognitive and behavioral domains remotely. Traditional cognitive rehabilitation is known to have some limitations related to the time, costs, and accessibility of patients to these services ( 61 – 63 ).…”
Section: Tele-cognitive-rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Technology-based treatments represent a promising field for multidisciplinary rehabilitation of children with acquired brain injury (ABI). Corti et al ( 22 ) underlined in a recent review that telerehabilitation is promising to enhance cognitive and behavioral domains remotely. Traditional cognitive rehabilitation is known to have some limitations related to the time, costs, and accessibility of patients to these services ( 61 – 63 ).…”
Section: Tele-cognitive-rehabilitationmentioning
confidence: 99%
“…Literature data shows that telerehabilitation can be a promising intervention for elderly ( 20 ), adults ( 21 ), children with neurological diseases ( 22 ), as well as for the treatment of motor ( 23 , 24 ), cognitive ( 25 ) and language disorders ( 26 – 30 ). In Italy, the healthcare system could be supported by telemedicine interventions, due to the aging population, the increase in chronicity and morbidity of diseases, and the presence of rural areas, islands, and mountains.…”
Section: Introductionmentioning
confidence: 99%
“…One key initiative is to give patients with TBI the opportunity to undergo rehabilitation even if they are discharged home after acute care, and rehabilitation programs may be conducted in day hospital or home settings. 45 Some of these programs may incorporate tele-rehabilitation, which has recently been developed in both pediatric and adult TBI populations, 46,47 and this may help overcome the problem of access to specialized rehabilitation services. As neurobehavioral changes are frequent after TBI, and as patients may show poor self-awareness, 48 initiating early multidisciplinary rehabilitation may help patients better understand their needs and the potential interest of physical or occupational therapy.…”
Section: Implications and Directions For Future Researchmentioning
confidence: 99%
“…the feasibility and accessibility of remote computerized cognitive training (CCT) for children with ABI have been documented 24,25 . Preliminary results on the efficacy of CCT in these children [14][15][16]26 or in children with neurodevelopmental disorders 27,28 have also been provided. A recent meta-analysis indicated that remote CCT programs based on the repetition of cognitive exercises (drill-based exercises) have an effect on the visual-spatial abilities of children with ABI, but no effects were documented for other cognitive abilities 26 .…”
mentioning
confidence: 99%
“…Preliminary results on the efficacy of CCT in these children [14][15][16]26 or in children with neurodevelopmental disorders 27,28 have also been provided. A recent meta-analysis indicated that remote CCT programs based on the repetition of cognitive exercises (drill-based exercises) have an effect on the visual-spatial abilities of children with ABI, but no effects were documented for other cognitive abilities 26 . Nevertheless, evidence of the effects on far transfer measures of CCT programs for children with ABI has been questioned 29,30 .…”
mentioning
confidence: 99%